Harry Potter complete collection 8 Filme - Rowling, J. K. 1965-; Williams, John 1932- (Warner Home Video Germany, 2004)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts School of Witchcraft and Wizardry. (www.imdb.com)
Bild 16:9 (2.35:1)
Original: Großbritannien, USA 2001
Keywords: Film; DVD-Video